THE TEST OF CHARACTER BY WAR AND TIME: A COMPARATIVE ANALYSIS OF V. RASPUTIN'S «LIVE AND REMEMBER», CH. AITMATOV'S «FACE TO FACE» AND S. AHMAD'S «HORIZON» (Spectrum Journal of Innovation, Reforms and Development, 2026)
This article undertakes a detailed comparative analysis of three notable works of Soviet literature created during the Thaw and Stagnation periods: Valentin Rasputin's novella «Live and Remember», Chingiz Aitmatov's novella «Face to Face», and Said Ahmad's novel «Horizon». The primary focus is on the problem of moral choice that the characters face in the difficult circumstances of wartime and in subsequent historical periods. The spatio-temporal characteristics of each work are examined. The article notes how the authors depict the internal conflict between a sense of duty and the voice of conscience, and what artistic means they use to convey this drama. The theme of changes in human character under the influence of trauma and upheaval, both military and social, is also considered. By analyzing these changes, we strive to understand what remains immutable in a person and which values prove to be the most resilient.